CHOICE OF EFFICIENT METHOD OF ADDING FLOUR FROM BUCKWHEAT BRAN - E. I. Ponomareva (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2015)
Nowadays the production of functional bakery products for therapeutic and preventive nutrition is of current importance. The problem of providing the population with functional products can be solved by enriching the recipes with vitamins, dietary fiber, micro and macronutrients. At the chair of "Technology of baking, confectionery, pasta and grain processing" of Voronezh State University of Engineering Technologies the recipe of no-salt bread from mixture of baker’s first grade wheat flour and whole-grain wheat with adding buckwheat bran flour, that increases the nutrition value of the product, has been developed. Flour from buckwheat bran is characterized by a high-scale balance of the content of essential amino acids, good digestibility, rich in vitamins (especially B vitamins, PP), dietary fiber, minerals (potassium, calcium, magnesium, iron). The use of buckwheat flour from the bran in bread production stimulates the creation of favorable intestinal microflora, normalizes blood sugar level, and excretes toxins, toxic salts and heavy metals from the body. We have conducted a research on how to make the rational choice of method of adding buckwheat bran flour enricher into dough from a mixture of first grade wheat flour and whole-grain wheat, compressed yeast and potable water, thus ensuring high and stable physical and chemical characteristics and the quality of the end product. Also, we have discovered that the bakery product prepared on tight sponge with addition of enricher has much better organoleptical properties in comparison with the others. Bread is characterized by a pleasant taste and flavour, elastic porous crumb. It has been found that the consumption of 100 g of a mixture of no-salt bread from first grade wheat flour and whole-grain with adding buckwheat bran flour will provide enough daily intake of protein 10.7%, fat 1.5%, carbohydrates 10.4% dietary fiber 16.3%, amino acids 2.5 14.0%. No-salt bread is recommended to people with cardiovascular diseases and renal insufficiency. According to the chosen efficient method of adding buckwheat bran flour in the dough for no-salt bread, we have found out that the method when enricher is added in the sponge provides the best physical and chemical, and structure mechanical properties of the bakery product and can be recommended for baking bread for mass production at the bakery plant.